Analysis of the regulatory framework in the innovative activity of industrial enterprises - Natalia Ulianycka (Cхід, 2013)
Analyzed the development of regulatory frameworks in innovation industries. Scientific-practical recommendations for future improvement of the state innovation policy in this area.